Experimental study on the thermal performance of solar air conditioning system with MEPCM cooling storage. (22nd January 2019) - Zheng, Lin; Zhang, Wei; Xie, Lingzhi; Wang, Wei; Tian, Hao; Chen, Mo
Abstract: Solar powered air conditioning system is a hot issue in the study field of building energy conservation. An experimental platform of solar powered air conditioning with microencapsulated phase change material (MEPCM) cooling storage system was carried out to evaluate the efficiency of the solar powered air conditioning system and the coupled relation with the solar radiation intensity. The outdoor and indoor environmental test system was used to collect the performance parameter data of test room to verify the cooling energy storage effect. The solar air conditioning combined with MEPCM cold storage system which was tested in Chengdu city, China. According to the analysis result, the transient thermal efficiency would decline with the rising normalized temperature difference. The transient thermal efficiency has the same variation trend with the solar radiation. The indoor air temperature of the test room was maintained between 18°C and 22°C. MEPCM cold storage system could maintain the indoor air temperature in the stable range. The energy saving rate of the completed system could reach at 30.5%. The research result could help to improve the study of solar powered air conditioning system and its application.